Clinico-bacteriological profile of lower respiratory tract infections in a tertiary care hospital in Kolkata – A cross-sectional and observational study - Somnath Bhunia; Surya Jyati Chaudhuri; Bithika Ghosh; Subhendu Sikdar; Abhiparna Roy; Ankita Das; Prasenjit Jana (Asian Journal of Medical Sciences, 2024)
Background: Lower respiratory tract infection (LRTI) is the most common infection causing significant mortality with a 3–5% death rate in adults. The emerging nature of antimicrobial resistance to pathogens makes its treatment more challenging and complicated for physicians. Aims and Objectives: The study was designed to obtain a comprehensive insight into the microbial profile and resistance patterns of the isolated pathogens in LRTI in a tertiary care hospital in Kolkata. Materials and Methods: The cross-sectional observational study was carried out in the Microbiology Department of N.R.S Medical College from January to December 2021. Specimens collected from 782 clinically suspected LRTI cases were processed as per standard laboratory protocol following clinical and laboratory standard Institute guidelines. Results: Out of 782 respiratory samples, 47.83% showed significant bacterial growth. The major risk factor was found to be type II diabetes mellitus (47.44%) followed by chronic obstructive pulmonary disease (36.57%) and smoking (21.35%). 85.56% growth was monomicrobial and Gram-negative organisms (88.50%) predominated. Klebsiella pneumoniae (36.90%) was the most predominant Gram-negative bacilli followed by Pseudomonas aeruginosa (17.11%) and Acinetobacter species (13.90%). Staphylococcus aureus was the predominant Gram-positive isolate (7.49%). Gram-negative organisms showed the highest resistance to penicillin and cephalosporins, whereas the lowest resistance in carbapenems. Piperacillin/tazobactam and levofloxacin showed good susceptibility. Linezolid was the most susceptible antimicrobial followed by vancomycin in the case of Gram-positive organisms. Extended-spectrum β-lactamase was detected as the mechanism of resistance in 31.12% of cases and carbapenemase was detected in 19.64% of cases. Conclusion: Increasing antimicrobial resistance and varied bacterial etiology make it necessary to develop appropriate antibiotic policy and implement antimicrobial stewardship for effective and prompt therapy.